Europe's New Whistleblowing Laws Research Papers from the 2nd European Conference on Whistleblowing Legislation - Gerdemann, Simon (Universitätsverlag Göttingen, 2023)
The "European Whistleblowing Directive" (Directive (EU) 2019/1937) is the most far-reaching piece of whistleblowing legislation in history with an unprecedented impact on countries all across the European Union. To transpose the Directive, all 27 Member States were required to enact their own national whistleblowing laws by 17 December 2021, in many cases leading to the creation of an entirely new field of law previously unknown to many national legal systems. The papers included in this book are the result of the "2nd European Conference on Whistleblowing Legislation", providing readers with a first in-depth look into the emerging field of research that is European Whistleblowing Law.